Peningkatan Hasil Belajar IPS dengan Metode Pembelajaran Snowball Throwing Di Sekolah Dasar - Anna Dwi Purwanti; Victor Novianto (UM Purwokerto Press, 2022)
This research is motivated by the low learning outcomes of students on the subject matter of Social Sciences (IPS). The learning outcome is caused by the teachers only using conventional learning methods and the student being less involved in the learning process. Therefore, teachers need to change the way of learning by using appropriate learning methods so that they are not dull. One of the learning methods used is the Snowball Throwing learning method. Students must be more responsive to receiving messages from others and conveying them to their group friends. A pleasant learning atmosphere makes maximum learning outcomes. This study aims to determine the improvement of social studies learning outcomes with the Snowball Throwing learning method in elementary schools. The subjects in this study were fifth-grade students at SDN Belang for the 2021/2022 academic year, with 21 students consisting of 12 male students and nine female students. The method used in this research is Classroom Action Research (CAR) which is carried out in two cycles. Data to determine students' social studies learning outcomes were collected using test results in multiple-choice tests and analysis with percentages. Based on the data analysis, the number of students who finished studying in the pre-cycle was 12 people or 57.14%, after the first cycle, there were 16 people or 76.19%, the second cycle was 19 people or 90.48%. These data indicate that cooperative learning with the Snowball Throwing method can improve social studies learning outcomes in elementary schools.